Anthropometric parameters' cut-off points and predictive value for metabolic syndrome in women from Cartagena, Colombia - Gustavo José Mora-García; Doris Gómez-Camargo; Enrique Mazenett; Ángelo Alario; Álvaro Fortich; Claudio Gómez-Alegría (Instituto Nacional de Salud Pública, 2014)
Objective. To estimate anthropometric parameters' (APs) cut-off points and association for metabolic syndrome (MetS). Materials and methods. A cross-sectional study was carried out with a total of 434 adult women from Cartagena de Indias, Colombia, in 2012. APs measured were waist circumference (WC), body mass index (BMI), body adiposity index (BAI), waist-hip ratio (WHR) and waist-height ratio (WHtR). Cut-off points were estimated by a receiver operating characteristic curve (ROC). Logistic regression was applied to estimate possible associations. Results. Cut-off points for WC, BMI, BAI, WHR and WHtR were 85 cm, 28 kg/m2, 39%, 0.80 and 56, respectively. Only WHtR was associated to MetS (OR=1.11, CI95% [1.07-1.15]). Conclusion. WC cut-off point was higher than those proposed for Latin-American women by the Joint Interim Statement (JIS). WHtR had a low predictive value for MetS.